Anxious and depressive symptoms mediate the influence of sleep quality on suicidality in young adults - Slanitz, Corinna; Fuchshuber, Jürgen; Fink, Andreas; Unterrainer, Human-Friedrich (Frontiers in Public Health, 2024)
This study investigated how sleep quality affects the global severity of psychiatric symptoms, including suicidality, in young adults. Poor sleep quality has a significant impact on mental health and should therefore be given special attention in suicidal treatment. 1214 participants (914 females; age: M = 25.81, SD = 6.35) completed the Brief Symptom Inventory (BSI-18), the Scale for Suicidal Experience and Behaviour (SSEV) and the Pittsburgh Sleep Quality Index (PSQI) via an online survey. Correlation statistics and path analysis were conducted for data evaluation. Thereby, anxiety and depression but not somatization mediated the relationship between sleep quality and suicidality. Our findings confirm the putative link between diminished sleep quality and increased suicidality and may lead to an early detection of suicidal behaviour.